PENGARUH PROGRAM GERAKAN SATU RUMAH SATU JUMANTIK TERHADAP ANGKA BEBAS JENTIK DAN JUMLAH KASUS DEMAM BERDARAH DENGUE DI UPTD. PUSKESMAS KUTA UTARA BADUNG - I Gede Nara Swara; Komang Yogi Triana (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
Dengue Hemorrhagic Fever (DHF) is one of the national priorities for controlling infectious diseases in Indonesia, therefore preventing the development of the Aedes aegypti mosquito as a dengue transmitter is absolutely necessary. One of the programs to increase the larva free rate and reduce DHF cases promoted by the government is one house one larva watcher movement program. This study aimed to determine the effect of the one house one larva watcher movement program on the larva free rate and the number of DHF cases in the Regional Technical Implementation Unit (RTIU) of Public Health Centre North Kuta Badung. This type of research was pre-experimental with Intact-Group Comparison design, the sample in this study was the head of the family who lived in Banjar Celuk and Gaji of the RTIU working area. Public Health Centre North Kuta Badung in accordance with the inclusion and exclusion criteria was selected by purposive sampling of 76 families consisted of 38 control group and 38 intervention group families. The research was conducted for 1 month. Data were analyzed with the nonparametric Mann Whitney test at a significance level of α 0.05, then p value was 0.000 <0.05 on the larva free rate variable and 0.007 <0.05 on the variable number of DHF cases, therefore it can be concluded there was an effect of the one house one larva watcher movement program on the larva free rate and the number of DHF cases in the Regional Technical Implementation Unit (RTIU) Public Health Centre North Kuta Badung It is expected that the community can play a more active role in preventing and handling DHF cases in their region by participating and being able to carry out the one house one larva watcher movement program. Keywords: Dengue Hemorrhagic Fever (DHF), Larva Free Rate, One House One Larva Watcher Movement